Surface morphology evaluation of multi-angle 2D ultrasonic vibration integrated with nanofluid minimum quantity lubrication grinding. (March 2020) - Gao, Teng; Zhang, Xianpeng; Li, Changhe; Zhang, Yanbin; Yang, Min; Jia, Dongzhou; Ji, Heju; Zhao, Yongjun; Li, Runze; Yao, Peng; Zhu, Lida
Highlights: Kinematics model and simulation of grain/workpiece relative motion in 2D UVAG at different θ were developed. Grain's cutting characteristics were conducive to the full infiltration of nanofluids into the grinding zone. The surface characterization of multi-angle 2D UVAG coupled with NMQL was evaluated experimentally. The results showed that the optimal θ was achieved at 45° due to differential cutting action of follow-up grain. Autocorrelation function curves presented periodic and continuous local oscillation under the conditions of θ=45°. Abstract: Nanofluid minimum quantity lubrication (NMQL) is an emerging cleaner and sustainable technique. However, the effective immersion of nanofluids in the grinding zone in NMQL grinding limits the extensive application of this technique. Ultrasonic vibration can exert a pumping effect that injects nanofluids into the interface between the grinding wheel and workpiece. Furthermore, technique integration benefits the infiltration state transition of micro-droplets. However, evaluation of the coupling effect and surface morphology of multi-angle 2D ultrasonic vibration integrated with NMQL has rarely been performed. This study aims to address these research limitations. A kinematics model was developed, and the grain and workpiece relative motion trails in 2D ultrasonic vibration-assisted grinding (UVAG) were simulated at different resultant vibration angles ( θ ). The grain's cutting characteristics were then analyzed and found to be conducive to the full infiltration of nanofluids into the grinding zone. Moreover, the surface characterization of multi-angle 2D UVAG coupled with NMQL was evaluated experimentally. Results showed that the optimal θ was achieved at 45° due to the differential cutting action of the follow-up grain. NMQL obtained a better result than flooding at the same θ . When the gain effect of the coupling techniques was reflected in surface roughness, the R a value decreased by 19.5 % (compared with UVAG) and 39.9 % (compared with NMQL). The autocorrelation function curves presented periodic and continuous local oscillations under the grinding conditions of 2D UVAG with θ = 45° and θ = 135°.